The Problem of Relativism in the Sociology of (Scientific) Knowledge - Seidel, Markus (Philosophische Analyse / Philosophical Analysis, 2011)
This volume comprises original articles by leading authors - from philosophy as well as sociology - in the debate around relativism in the sociology of (scientific) knowledge. Its aim has been to bring together several threads from the relevant disciplines and to cover the discussion from historical and systematic points of view. Among the contributors are Maria Baghramian, Barry Barnes, Martin Endreß, Hubert Knoblauch, Richard Schantz and Harvey Siegel.